Theoretical Foundations of Gen AI-informed Teacher Pedagogy (London Journal of Research In Humanities and Social Sciences, 2025)
The integration of Generative Artificial Intelligence (GenAI) into educational pedagogy represents a transformative shift in the dynamics of teaching and learning. To guide this transition, this paper introduces the Ped-AI-gogy Informed Model (PIM), which combines established educational frameworks: the Technology Acceptance Model (TAM), the SAMR model, and Technological Pedagogical Content Knowledge (TPACK), into a cohesive approach for GenAI integration. This model provides a progressive pathway for educators, moving from initial awareness to active advocacy, while addressing the complexities of technology adoption, pedagogical change, and shifting educator-learner relationships.In addition, this paper develops the theoretical foundation of “ped-AI-gogy”, a concept that fuses pedagogy with AI to reimagine teaching practices in an increasingly digital landscape. By situating this integration within a posthumanist perspective, the authors advocate for a collaborative, symbiotic relationship among educators, students and GenAI tools. Finally, the paper critiques traditional human-centred educational paradigms and calls for adaptive learning models that harness GenAI potential to enhance both teaching and learner agency
Keywords: Human Rights; Cultural relativism; Human rights watch; Inherited; Male guardianship; Al Shafallah.; justice.; Justice Administration; Courts of First Instance; Court Organisation; Judicial Institution; Integration; Pedagogy; Generative Artificial Intelligence (GenAI); posthumanist